Towards a more effective legal framework for investor-state arbitration in Nigeria - Aluko, Adebowale (Department of Commercial Law, 2021)
There has been a backlash against the Investor State Dispute Settlement (ISDS) system in recent times. Amongst other complaints, critics have argued that the ISDS whittles down the regulatory powers of states in favour of private adjudicators. These criticisms are premised on the fact that unlike commercial arbitration, investment arbitration awards may have far reaching effects on states. In response to these concerns, the United Nations Commission on International Trade Law (UNCITRAL) Working Group III and other similar bodies have been tasked to carry out reforms to address some of these issues. In spite of ongoing reforms, criticisms have continued with some countries abandoning the investor-state arbitration mechanism altogether. In Nigeria, the state of crisis in the judiciary has necessitated the need for a viable alternative to litigation. The ISDS framework therefore remains the preferrable option for the resolution of investment disputes. There have been recent attempts to amend the Arbitration and Conciliation Act 11 of 1988. Also, the Nigerian Investment Promotion Commission recently announced plans to reform the country's investment law framework. It is in the light of these developments that this research has been undertaken to examine the flaws in Nigeria's investment arbitration framework and reforms that may be introduced to address them. In making a case for the retention of the ISDS framework in Nigeria, this study critiques Nigeria's investment arbitration framework and explores a number of recommendations towards addressing current challenges. It is argued that the proposed solutions will improve the effectiveness of Nigeria's investment arbitration framework especially with respect to the legal framework for the consent of the Nigerian government to ICSID arbitration and in the area of court assisted measures and post-arbitral award litigation.